Ziarah di Mandailing Natal: Identitas Religius, Keberlanjutan Budaya, dan Pariwisata Warisan Budaya Islam - Ahmad Muhajir (Medan Resource Center, 2025)
This article explores the phenomenon of pilgrimage in Mandailing Natal, emphasizing the practice of visiting the tombs of Islamic scholars (ulama) as an essential part of the region’s religious and cultural landscape. The pilgrimage tradition in Mandailing Natal is closely intertwined with the presence of Islamic educational institutions such as pesantren (Islamic boarding schools), which shape the community’s patterns of piety, reverence, and spiritual devotion toward their religious teachers. Using a qualitative descriptive method that includes field observation, interviews, and literature review, this study finds that religious tourism serves not only as a spiritual journey but also as a medium for cultural preservation and community identity reinforcement. The pilgrimage activities affirm the moral continuity between teachers and students and demonstrate the enduring strength of Islamic values in Mandailing Natal. The conclusion highlights the theoretical and practical contributions of this study to the field of heritage tourism, showing that pilgrimage traditions in Mandailing Natal not only sustain local spirituality but also offer a framework for developing culturally grounded and sustainable heritage tourism models in Islamic contexts.